2007
DOI: 10.1158/1535-7163.mct-06-0634
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the apoptotic machinery in pancreatic cancers using small-molecule antagonists of the X-linked inhibitor of apoptosis protein

Abstract: Resistance to apoptosis is a hallmark of many solid tumors, including pancreatic cancers, and may be the underlying basis for the suboptimal response to chemoradiation therapies. Overexpression of a family of inhibitor of apoptosis proteins (IAP) is commonly observed in pancreatic malignancies. We determined the therapeutic efficacy of recently described small-molecule antagonists of the X-linked IAP (XIAP) in preclinical models of pancreatic cancer. Primary pancreatic cancers were assessed for XIAP expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 48 publications
5
55
1
Order By: Relevance
“…3 A and B). This effect was most pronounced in FG-3019/ gemcitabine combination-treated mice, consistent with the ability of Xiap silencing (33) or Xiap chemical inhibition (34) to sensitize PDA cell lines to additional therapies. Xiap mRNA levels were also significantly reduced by FG-3019 in the presence and absence of gemcitabine (Fig.…”
Section: Fg-3019 Decreases Expression Of X-linked Inhibitor Of Apoptosupporting
confidence: 75%
“…3 A and B). This effect was most pronounced in FG-3019/ gemcitabine combination-treated mice, consistent with the ability of Xiap silencing (33) or Xiap chemical inhibition (34) to sensitize PDA cell lines to additional therapies. Xiap mRNA levels were also significantly reduced by FG-3019 in the presence and absence of gemcitabine (Fig.…”
Section: Fg-3019 Decreases Expression Of X-linked Inhibitor Of Apoptosupporting
confidence: 75%
“…Beyond CLL, XIAP inhibitors have recently been reported by our group and other investigators to act in concert with TRAIL to trigger apoptosis in childhood acute leukemia, pancreatic, colon, or breast carcinoma cells (29,43,44). In addition, low-molecular weight Smac mimetics displayed antitumor activities as single agents in multiple myeloma and several solid cancers (45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we demonstrated that neutralizing XIAP either by RNA interferencemediated knockdown or by small molecule inhibitors acted in concert with soluble recombinant TRAIL to induce apoptosis in pancreatic cancer in vitro and in vivo (16)(17)(18). In addition, XIAP small molecule antagonists that target the BIR2 domain of XIAP were reported to synergize with TRAIL in pancreatic cancer (17,43). Compared with these earlier reports that focus on soluble recombinant TRAIL, the current study shows for the first time that the antitumor activity of TRAIL receptor-specific antibodies is profoundly enhanced by neutralizing XIAP in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%